2018
DOI: 10.1080/10376178.2018.1492350
|View full text |Cite
|
Sign up to set email alerts
|

Determining nurses’ perceptions of patient safety culture in palliative care centres

Abstract: Patient safety culture is related to nurses' working conditions and the attitude of management towards errors, etc. The results of this study will provide a contribution to the development of healthcare and healthcare training policies for critical units vulnerable to patient safety violations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
2
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
1
3
2
1
Order By: Relevance
“…Weaknesses in work environments have been shown to be associated with an increase in patient mortality, readmissions, and the risk of adverse events. 32,33 In this study, rates for the working conditions domain were unsatisfactory, which corroborates findings in relevant literature. 23,26 Moreover, participants indicated they were disappointed and exhausted by their work.…”
Section: Discussionsupporting
confidence: 90%
“…Weaknesses in work environments have been shown to be associated with an increase in patient mortality, readmissions, and the risk of adverse events. 32,33 In this study, rates for the working conditions domain were unsatisfactory, which corroborates findings in relevant literature. 23,26 Moreover, participants indicated they were disappointed and exhausted by their work.…”
Section: Discussionsupporting
confidence: 90%
“…Palliative care clinicians in this study strongly perceived that error reporting was encouraged and expected in their service, and stated they felt safe to do so. However, the non-punitive error reporting culture identified in this study differs from other studies in health care services (Boyer, McPherson, Deshpande, & Smith, 2009;Castel, Ginsburg, Zaheer, & Tamim, 2015;Dincer, Torun, & Aksakal, 2018;Khalil & Lee, 2018). A Turkish study of palliative care nurses' perceptions of safety culture found almost half (48%) reported that hospital management response to an error was punitive (Dincer et al, 2018).…”
Section: Discussioncontrasting
confidence: 82%
“…However, the non-punitive error reporting culture identified in this study differs from other studies in health care services (Boyer, McPherson, Deshpande, & Smith, 2009;Castel, Ginsburg, Zaheer, & Tamim, 2015;Dincer, Torun, & Aksakal, 2018;Khalil & Lee, 2018). A Turkish study of palliative care nurses' perceptions of safety culture found almost half (48%) reported that hospital management response to an error was punitive (Dincer et al, 2018). These nurses perceived that errors reflected an inability to carry out their professional role and thought they would be judged by their peers and punished by management (Dincer et al, 2018).…”
Section: Discussioncontrasting
confidence: 73%
See 1 more Smart Citation
“…Zaten PB merkezlerinde yatan hastaların büyük çoğunluğunun karar verme kapasiteleri azalmış durumdadır. 27 Eğer hukuki bir düzenlemeye ihtiyaç varsa bu noktadan öncesini yani karar verme kapasitesinin azalmasından öncesini kapsamalıdır.…”
Section: Discussionunclassified